Product Innovation in Increasing Customer Loyalty in MSMEs Weaving Ikat Mas Medal in Kediri City - Dewi, Triasita; Samari, Samari (Universitas Nusantara PGRI Kediri, 2025)
This research explores the role of product innovation in increasing customer loyalty in MSMEs Weaving Ikat Medali Mas, Kediri City. Using a qualitative case study approach, data was collected through interviews, observations, and documentation. The findings suggest that innovations such modernizing traditional designs, diversifying products (e.g., bags and accessories), and incorporating sustainable materials are essential in fostering loyalty. Customers value the blend of tradition and modernity, digital accessibility, and personalized service. Telling stories about product heritage and sustainable practices strengthens emotional bonds, while a positive buying experience builds lasting relationships. The research highlights the importance of integrating cultural preservation with contemporary market demands, offering practical insights for MSMEs to digital marketing, sustainable practices, and designer collaboration to increase customer engagement and loyalty. Limitations include focus on single MSME, which presents opportunities for broader comparative studies in future research. Keywords: Product Innovation, Customer Loyalty, Traditional Crafts, Sustainable Practices, Digital Marketing